Acidity‐Activatable Dynamic Nanoparticles Boosting Ferroptotic Cell Death for Immunotherapy of Cancer. Issue 31 (25th June 2021) - Song, Rundi; Li, Tianliang; Ye, Jiayi; Sun, Fang; Hou, Bo; Saeed, Madiha; Gao, Jing; Wang, Yingjie; Zhu, Qiwen; Xu, Zhiai; Yu, Haijun
Abstract: Immunotherapy shows promising therapeutic potential for long‐term tumor regression. However, current cancer immunotherapy displays a low response rate due to insufficient immunogenicity of the tumor cells. To address these challenges, herein, intracellular‐acidity‐activatable dynamic nanoparticles for eliciting immunogenicity by inducing ferroptosis of the tumor cells are engineered. The nanoparticles are engineered by integrating an ionizable block copolymer and acid‐liable phenylboronate ester (PBE) dynamic covalent bonds for tumor‐specific delivery of the ferroptosis inducer, a glutathione peroxidase 4 inhibitor RSL‐3. The nanoparticles can stably encapsulate RSL‐3 inside the hydrophobic core via π–π stacking interaction with the PBE groups at neutral pH (pH = 7.4), while releasing the payload in the endocytic vesicles (pH = 5.8–6.2) by acidity‐triggered cleavage of the PBE dynamic covalent bonds. Furthermore, the nanoparticles can perform acid‐activatable photodynamic therapy by protonation of the ionizable core, and significantly recruit tumor‐infiltrating T lymphocytes for interferon gamma secretion, and thus sensitize the tumor cells to RSL‐3‐inducible ferroptosis. The combination of nanoparticle‐induced ferroptosis and blockade of programmed death ligand 1 efficiently inhibits growth of B16‐F10 melanoma tumor and lung metastasis of 4T1 breast tumors, suggesting the promising potential of ferroptosis induction for promoting cancer immunotherapy. Abstract : Intracellular‐acidity‐activatable nanoparticles integrating dynamic covalent bonds are developed for tumor‐specific delivery of glutathione peroxidase 4 (GPX4) inhibitor RSL‐3 and photodynamic therapy (PDT). Nanoparticle‐based GPX4 inhibition and PDT significantly promote the ferroptotic death of tumor cells and activate the T‐cell immune response for inhibiting tumor growth and suppressing distant metastasis.